2020
DOI: 10.1108/ecam-05-2020-0333
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of preconstruction factors in sustainable project management performance

Abstract: PurposeThe construction sector has a global reach, and construction professionals worldwide often encounter challenges in delivering a project on time and within the assigned budget. Hence, this paper aims to investigate the preproject factors that most affect the performance of construction projects.Design/methodology/approachA literature review was conducted to identify these factors from previous research, after which a questionnaire was developed and distributed to construction industry professionals world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
(31 reference statements)
0
10
0
1
Order By: Relevance
“…Cronbach's alpha was used to provide an estimate of the internal consistency of the test, which describes the extent to which all items in a test measure the same concept or construct; hence, it is connected to the inter-relatedness of the items within the test (Brown, 2002;Tavakol and Dennick, 2011). Since values of 0.7 and above are accepted, Cronbach's alpha values were calculated for different categories separately and for the whole of the categories to check the reliability of the questionnaire (Naji et al, 2021); the results are shown in Table 4. Because all values are above 0.7, the reliability of the questionnaire was confirmed.…”
Section: Methodology and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cronbach's alpha was used to provide an estimate of the internal consistency of the test, which describes the extent to which all items in a test measure the same concept or construct; hence, it is connected to the inter-relatedness of the items within the test (Brown, 2002;Tavakol and Dennick, 2011). Since values of 0.7 and above are accepted, Cronbach's alpha values were calculated for different categories separately and for the whole of the categories to check the reliability of the questionnaire (Naji et al, 2021); the results are shown in Table 4. Because all values are above 0.7, the reliability of the questionnaire was confirmed.…”
Section: Methodology and Data Collectionmentioning
confidence: 99%
“…The Mann-Whitney U test is a non-parametric statistical technique used to analyze differences between the medians of two data sets (Milenovic, 2011). To compare more than two independent samples, the Kruskal-Wallis method, a general non-parametric test, is used for determining important differences between groups, which are continuous independent or ordinal dependent variables (Ostertagova et al, 2014;Naji et al, 2021).…”
Section: Methodology and Data Collectionmentioning
confidence: 99%
“…The support system model was clustered into three stages: 1) investigating, 2) studying the different choices and proposals, and 3) dominance building. Support system and predictive frameworks with respect to construction industry viewpoint were developed to assess managerial practices through identification of factors im-pacting construction engineering management (Viswanathan & Jha, 2019;Castillo et al, 2018;Pereira et al, 2018;Ghodrati et al, 2018;Hasan et al, 2018;Ibrahim et al, 2020a;Naji et al, 2020). Choi et al (2020) developed a decision support model for determining the effects of alternative contracting methods on project time-cost performance.…”
Section: Adopted Change Order Management In the Literaturementioning
confidence: 99%
“…The construction industry has the potential to contribute to society by providing the required infrastructure and employment opportunities. In addition, it can also help reduce emissions, reduce the consumption of raw materials and cost saving by using the material waste generated during construction activities (Naji et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%